prime minister decree no 1299/2015 on forming the committee for settlement of investment contract disputes = قرار رئيس مجلس الوزراء رقم 1299 لسنة 2015 بتشكيل لجنة تسوية منازعات عقود الاستثمار - Egypt; The middle east library for economic services, translator. (2025)
Prime Minister Decree No. 1299 Of The Year 2015 قرار رئيس مجلس الوزراء رقم 1299 لسنة 2015